Examining the Relationship Between Brand Satisfaction and Customer Experience in Nepal's Retail Banking Sector - Karna, Poonam Kumari Labh (Darul Yasin Al Sys, 2025)
This study examines the primary determinants of customer happiness and loyalty in Nepal's competitive retail banking industry. By integrating insights from primary data and existing literature, this study investigates the effects of situational factors (frequency of bank visits, length of customer-bank relationship) and service quality dimensions (tangibility, reliability, responsiveness, assurance, and empathy) on customer satisfaction and subsequent loyalty. Information was gathered from 575 customers of